PENGARUH PERILAKU NARSIS DAN SELF-ESTEEM TERHADAP PENGENDALIAN DIRI AKUNTAN DALAM BERINTERAKSI DI MEDIA SOSIAL DENGAN ETIKA PROFESI AKUNTAN SEBAGAI VARIABEL INTERVENING - Nurbaeti Nurbaeti (Universitas Pamulang, 2019)
This research is conducted to investigate the effect of narcissism and self-esteem toward the accountants’ self control in the interaction in social media with accountant professional ethics as an intervening variabel. The method of the research used is causality-explanatory to analyze as well as to prove that ther is a correlation among two or more variables. The object of this research are 100 people as respondents, they are educators, auditors and accountants in some companies in Tangerang and Jakarta. The technique used in taking samples is purposive sampling. This research used Narcissistic Personality Inventory (NPI-16), Rosenberg Self-Esteem Ten Scales, Accountants professional ethics and accountants self control scale. The method of data analaysis used is Path Analysis. The data that the researcher got has meet the prerequisite to do the test of data quality and classic assumption. The series of data analysis using SPSS version 23 got that narcissism and self-esteem affect the accountants professional ethics simultaneously and significantly, while self-esteem significantly affects the professional ethics of accountants. Narcissism, self-esteem and accountant professional ethics affect simultaneously toward accountants’ self control, narcissism does’nt effect significantly toward accountants’ self control and accountants professional ethics affects significantly toward their self control. The determination coefficient shows 10,3% of accountants’ self control variable affected by their narcissism, self-esteem and their ethics, while the rest 89,7% affected by other factors.